AI-Powered Closed-Loop Fusion: Demand-Technology-Implementation Synergy Across Business, Finance, and Cybersecurity (2022-2026) - Wang, Mei (International Journal of Multidisciplinary Research, 2026)
The cross-domain integration of artificial intelligence (AI) has formed a dynamic closed-loop ecosystem among digital commerce, finance, and cybersecurity—driven by mutually reinforcing demand pull, technical spillover, and implementation feedback. This review synthesizes 7 key studies (2022-2026) to unpack the "demand-technology-implementation" (DTI) closed-loop logic: digital commerce’s demand for inclusive growth and privacy protection spurs AI technical innovation; financial sector’s need for resource optimization and ESG compliance adopts and refines these technologies; cybersecurity’s requirement for risk balance provides safeguards for technical 落地；and implementation outcomes from all three domains feed back to refine AI solutions. Findings reveal that: privacy-enhancing technologies (PETs) and modular AI architectures are the core technical bridges; SMEs act as the key link for inclusive value diffusion; and risk-cost balance is the common optimization target. This closed-loop framework explains how AI enables seamless fusion across business, finance, and cybersecurity, offering guidance for researchers designing cross-domain AI and practitioners building integrated ecosystems.